Altered cortical network dynamics during observing and preparing action in patients with corticobasal syndrome - Marius Krösche; Christian J. Hartmann; Markus Butz; Alfons Schnitzler; Jan Hirschmann (Neurobiology of Disease)
Corticobasal syndrome (CBS) is characterized not only by parkinsonism but also by higher-order cortical dysfunctions, such as apraxia. However, the electrophysiological mechanisms underlying these symptoms remain poorly understood.To explore the pathophysiology of CBS, we recorded magnetoencephalographic (MEG) data from 17 CBS patients and 20 age-matched controls during an observe-to-imitate task. This task involved observing a tool-use video (action observation), withholding movement upon a Go cue (movement preparation), and subsequently imitating the tool-use action. We analyzed spectral power modulations at the source level.During action observation, event-related beta power (13-30 Hz) suppression was weaker in CBS patients compared to controls. This reduction was evident bilaterally in superior parietal, primary motor, premotor and inferior frontal cortex. During movement preparation, beta power suppression was also reduced in CBS patients, correlating with longer reaction times. Immediately prior to movement onset, however, beta suppression was comparable between groups.Our findings suggest that action observation induces beta suppression, likely indicative of motor cortical disinhibition, which is impaired in CBS patients. This alteration may represent a neural correlate of disrupted visuo-motor mapping in CBS. The altered timing of beta suppression to the Go cue suggests deficits in learning the task's temporal structure rather than in movement initiation itself.